Induction of Human Motor Cortex Plasticity by Theta Burst Transcranial Ultrasound Stimulation. Issue 2 (12th January 2022) - Zeng, Ke; Darmani, Ghazaleh; Fomenko, Anton; Xia, Xue; Tran, Stephanie; Nankoo, Jean‐François; Shamli Oghli, Yazan; Wang, Yanqiu; Lozano, Andres M.; Chen, Robert
Abstract : Objective: Transcranial ultrasound stimulation (TUS) is a promising noninvasive brain stimulation technique with advantages of high spatial precision and ability to target deep brain regions. This study aimed to develop a TUS protocol to effectively induce brain plasticity in human subjects. Methods: An 80‐second train of theta burst patterned TUS (tbTUS), regularly patterned TUS (rTUS) with the same sonication duration, and sham tbTUS was delivered to the motor cortex in healthy subjects. Transcranial magnetic stimulation (TMS) was used to examine changes in corticospinal excitability, intracortical inhibition and facilitation, and the site of plasticity induction. The effects of motor cortical tbTUS on a visuomotor task and the effects of occipital cortex tbTUS on motor cortical excitability were also tested. Results: The tbTUS produced consistent increase in corticospinal excitability for at least 30 minutes, whereas rTUS and sham tbTUS produced no significant change. tbTUS decreased short‐interval intracortical inhibition and increased intracortical facilitation. The effects of TMS in different current directions suggested that the site of the plastic changes was within the motor cortex. tbTUS to the occipital cortex did not change motor cortical excitability. Motor cortical tbTUS shortened movement time in a visuomotor task. Interpretation: tbTUS is a novel and efficient paradigm to induce cortical plasticity in humans. It has the potential to be developed for neuromodulation treatment for neurological and psychiatric disorders, and to advance neuroscience research. ANN NEUROL 2022;91:238–252